Mathematical education of young and adults: pedagogical implications of historical-cultural theory - Miguel, Jose Carlos [UNESP] (Univ Federal Tocantins, Campus Tocantinopolis, 2018)
The present study addresses some pedagogical implications of historical-cultural theory for the exploration of mathematical ideas in the field of youth and adult education (EJA). Starting from an analysis of the state of the art regarding the difficulties of teachers and students for teaching and learning of Mathematics throughout the schooling process indicates elements to the debate that return to the explanation of the problems listed and to refer a process of constitution of mathematical learning subjects within the scope of the EJA. It is a bibliographical and documentary research, besides the analysis of usual mathematical situations in EJA classes, whose results show the difficulties of the basic school culture to overcome didactic actions still strongly marked by the association of models. It points to the theoretical construct of the historical-cultural perspective as a perspective for the realization of a broad process of production of meanings and negotiation of meanings of teaching and learning of Mathematics in the EJA.
Keywords: Youth and Adult Education; EJA; Mathematical Education; Formation of Concepts; Production of Meanings; Negotiation of Mathematical Meanings